The Socio Demographic Status of Small Scale Fishers of Inland Open Water Area: A Case Study from Chalan Beel Area of Bangladesh - Sadekin, Md Nazmus; Ali, Jamal; Islam, Rabiul (International Journal of Engineering and Technology, 2018)
Fisheries are significantly contributing to the different aspects of a community such as livelihoods, supplying of food and ensuring security of food at both local and global levels. It also provides a vital source of protein as well as cash income for many families in the developing world. Though, fisheries sector is supporting about 11% of the total population’s livelihood of Bangladesh but fisherman is one of the most vulnerable communities in Bangladesh. Moreover, like other developing countries in Bangladesh, small-scale fisheries (SSFs) are making significant support regarding food nutrition and ensuring food security, alleviating poverty and sustainable livelihoods of the people. However, the livelihood of SSFs are undervalued both in the global and national scale by the scholars. Considering the above fact, it is very necessary to overview the current livelihood status of small scale fishing communities of inland open water area of Bangladesh. This study discussed the socio demographic status of SSFs in the Chalan Beel area of Bangladesh. Using a primary data survey this study discussed the SSF household head’s sex, age, marital status, education, household size, household dependency ratio, livelihood, general health, food and water management and social networking, for three upazilas (subdistricts) which are part of Chalan Beel of Bangladesh.